Exophiala psychrophila: A new agent of chromoblastomycosis (2019)
Chromoblastomycosis is a chronic cutaneous and subcutaneous mycosis, is caused by dematiaceous fungi, the most frequently implicated are Fonsecaea, Phialophora, Cladophialophora, Rhinocladiella and Exophiala. We report a woman who was treated before with mycological cure, but she experience a relapse requiring treatment again. Direct microscopic examination and skin biopsy with culture were necessary to identify a Exophiala psychrophila, and for our knowledge this is the first case reported.